Effect of oil cake amendment of soil on tomato wilt caused by Fusarium oxysporum f.sp. lycopersici - I.J. KAPOOR, HARENDER RAJ and (Indian Phytopathology, 2002)
Oil cakes, from groundnut, mustard, sesame and cotton seed, were assessed for their ability to reduce wilt of tomatoes caused by F. oxysporum f.sp. lycopersici. Groundnut and mustard at a 2% concn in soil (w/w) were most effective at reducing the pathogen population (>70%) and disease incidence. However, groundnut was superior to mustard as it not only reduced a higher disease index (77.1%) but it also improved plant growth. Cotton seed cake was the least effective. In root free soil, amendment with oil cakes reduced the activity of F. oxysporum f.sp. lycopersici and the magnitude of inhibition increased with decomposition over a period of 45 days.